The Effectiveness of Graphic Organizers in Improving Written Expression Skills Among Students With Learning Disabilities - Al-Zboun , Ahmed; Al-Natour, Mayada (Jordan Journal of Educational Sciences, 2017)
The purpose of this study was to investigate the effectiveness of graphic organizers in improving written expression skills among students with learning disabilities. The study sample consisted of (30) students in 5th grade with learning disabilities at schools of Mafraq district; (15) of them as an experimental group, and the other (15) as a control group. The experimental group was subjected to the teaching method which consisted of (26) training sessions. The tools that were used to collect data were a test of written expression and a scale of written expression skills. The results revealed statistically significant effect attributed to the teaching method that was based on graphic organizers in improving written expression for the fields of format and content on the post-test in favor of the experimental group. The result showed the positive effect of the teaching method which was used. The study recommended applying the teaching method based on graphic organizers in improving written expression among students with learning disabilities, and adding studies to investigate the effectiveness of graphic organizers in improving other skills such as reading comprehension